Question of the ZrO₂ – TiO₂ phase diagram - Logvinkov , Sergey M.; Borysenko, Oksana M.; Klochko, Natalja P.; Shabanova, Halyna M.; Shumeiko, Vita M. (Національний технічний університет "Харківський політехнічний інститут", 2025)
Ceramic materials based on zirconium dioxide (ZrO₂) occupy leading positions among m odern structural and functional materials due to their unique physical and chemical properties. These properties are due to the possibility of controlled stabilization of polymorphic modifications of ZrO₂ (monoclinic, tetragonal and Partiall y stabi lized zirconia exhibits high chemical inertness, low thermal conductivity, exceptional corrosion resistance and thermal shock resistance. These properties make ZrO₂ based ceramics promising for use in a wide range of fields, including biomedical, el ectroni c, structural and functional ceramics, as well as abrasives, refractories and insulation materials. One of the key problems w hen using pure ZrO₂ is the phase transition from the tetragonal to the monoclinic modification, accompanied by a significant change in the volume of the crystal lattice, which can lead to the destruction of the material. To prevent this transition, modifiers are used that form solid solutions with tetragonal ZrO₂, providing a metastable state due to distortions in the crystal s tructur e. Among such modifiers, titanium dioxide (TiO₂) occupies a special place. Joint doping of ZrO₂ with TiO₂ allows achieving specific effects, especially in the field of electroceramics, where un ique dielectric properties of finished materials based o n these oxides are manifested, which makes the ZrO₂ TiO₂ system an object of increased interest for researchers and engineers. The phase diagram of the ZrO₂ TiO₂ system has been studied since the 1950s, and during this time it has undergone significant refine ments. Modern research continues to improve it, but the use of a small scale to display the full diagram over the entire temp erature range has led to graphical inaccuracies, which complicates its application in technological practice. In this paper, a comp rehensive analysis of the phase diagrams is performed, based on the generalization of data from various studies. Керамічні матеріали на основі діоксиду цирконію (ZrO₂) займають лідируючі позиції серед сучасних конструкційних та функціонал ьних матеріалів завдяки своїм унікальним фізико хімічним властивостям. Ці властивост і обумовлені можливістю контрольованої стабілізації поліморфних модифікацій ZrO₂ (моноклінної, тетрагональної та кубічної). Частково стабілізований діоксид цирконію демонструє в исоку хімічну інертність, низьку теплопровідність, виняткову корозійну стійкіст ь та стій кість до термічних ударів. Ці якості роблять кераміку на основі ZrO₂ перспективною для застосування в широкому спектрі областей, включаючи біомедичну, електронну, конструкційну та функціональну кераміку, а також як абразивні, вогнетривкі та ізоляц ійні матеріали. Однією з ключових проблем при використанні чистого ZrO₂ є фазовий перехід з тетрагональної в моноклінну модифікацію, що супроводжується значною зміною об'єму кристалічних ґрат, що може призводити до руйнування матеріалу. Для запобі гання цьо му перехо ду застосовуються модифікатори, які утворюють тверді розчини з тетрагональним ZrO₂, забезпечуючи метастабільний стан за рахунок виникнення дефектів у кристалічній структурі. Серед таких модифікаторів особливу увагу займає діоксид титану (TiO₂). Сп ільне допування ZrO₂ з TiO₂ дозволяє досягти специфічних ефектів, особливо в галузі електрокераміки, де проявляються унікальні діелектричні властивості готових матеріалів на основі даних оксидів, що робить систему ZrO₂ TiO₂ об'єктом підвищеного інтересу для дослі дників та інженерів. Діаграма стану системи ZrO₂ TiO₂ вивчалася з 50 х років, і за цей час вона зазнала значних уточнень.
До питання про діаграму стану ZrO₂ – TiO₂
Keywords: zirconium dioxide; titanium dioxide; phase equilibria; modification; solid solutions; ceramics; phase diagram; synthesis of materials; діоксид цирконію; діоксид титану; фазові рівноваги; модифікація; тверді розчини; кераміка; діаграма стану; синтез